White Painting Pigment as a Low-Cost Light Scattering Material for Bilayer Photoelectrodes of Dye-Sensitized Solar Cells - Joshi, P. (Journal of Nepal Physical Society, 2019)
White pigment (DuPont R902+) has been used as a light scattering material in the preparation of bilayerphotoelectrodes of dye-sensitized solar cells (DSCs). The X-ray diffraction (XRD) pattern of the white pigment revealed that the material consists of rutile phase of titanium dioxide. The light scattering layer prepared from the white pigment was coated onto the main-layer of the photo electrodes of DSCs. The solar cells with and without light scattering layer were tested in the simulated light of 100 mW/cm2. The DSCs with the light scattering layer generated more current density than the DSCs without scattering layer and the overall light to electric power conversion efficiency of DSCs with the light scattering layer was 4.00 % compared with 3.25 % efficiency of the DSCs without the scattering layer.